Case reports of benign intrascrotal tumors: Two epidermoid cysts and one scrotal calcinosis - ŞEKERCİ, ÇAĞRI AKIN (PAGEPRESS PUBL, 2020)
Background: The aim this study was to explain the underlying etiology of unknown scrotal masses. Case presentation: This study included 3 patients with a intrascrotal mass. One patient was over 50 years. The remaining patients were between the ages of 30-50. Patients had no serious complaints (two complained about having 3 testicles and one complained of swelling in the scrotum for the last 6 months). All patients underwent scrotal exploration under general anesthesia and the specimen was sent for pathological examination. All masses were mobile and encapsulated. The masses were not associated with the testicle. Two cases had classical histologic features of epidermoid cyst and one had scrotal calcinosis in the pathological report. Physical examination, operation, magnetic resonance and histological images of scrotal masses were shown in the figures. Conclusions: This study is important in terms of showing the underlying etiology of the rare scrotal masses.
Keywords: Intrascrotal; Epidermoid cyst; Calcinosis cutis